Assessing support for substance use policies among the general public and policy influencers in two Canadian provinces - Curtin, Kimberley D.; Thomson, Mathew; Hyshka, Elaine; Colman, Ian; Wild, T. C.; Belon, Ana P.; Nykiforuk, Candace I. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Examining support for substance use policies, including those for harm reduction, among the general public and policy influencers is a fundamental step to map the current policy landscape and leverage policy opportunities. Yet, this is a knowledge gap in Canada. Our paper identifies the level of support for substance use policies in two provinces in Canada and describes how the level of support is associated with intrusiveness and sociodemographic variables. Methods Data came from the 2019 Chronic Disease Prevention Survey. The representative sample included members of the general public (Alberta n = 1648, Manitoba n = 1770) as well as policy influencers (Alberta n = 204, Manitoba n = 98). We measured the level of support for 22 public policies concerning substance use through a 4-point Likert-scale. The Nuffield Council on Bioethics Intervention Ladder framework was applied to assess intrusiveness. We used cumulative link models to run ordinal regressions for identification of explanatory sociodemographic variables. Results Overall, there was generally strong support for the policies assessed. The general public in Manitoba was significantly more supportive of policies than its Alberta counterpart. Some differences were found between provinces and samples. For certain substance use policies, there was stronger support among women than men and among those with higher education than those with less education. Conclusions The results highlight areas where efforts are needed to increase support from both policy influencers and general public for adoption, implementation, and scaling of substance use policies. Socio-demographic variables related to support for substance use policies may be useful in informing strategies such as knowledge mobilization to advance the policy landscape in Western Canada.